Pilot study on seasonal variability in microbial contamination in the developing tourist region of Mindo, Ecuador: a comparative analysis of the Saguambi, Mindo, and Canchupí Rivers - Milena Naomi Martínez-Játiva; Pamela Borja-Serrano; Hugo Valdebenito; António Machado (BMC Research Notes)
Abstract Objective This study aims to evaluate the microbial load in the Saguambi, Mindo, and Canchupí Rivers in Mindo (Ecuador) by quantifying bacteriological indicators (Escherichia coli and total coliforms) and identifying pathogenic microorganisms (e.g., Giardia, Cryptosporidium spp., Helicobacter pylori, Mycobacterium tuberculosis, and Mycobacterium leprae) using molecular techniques. This assessment aims to establish the potential risk associated with the consumption and recreational use of these water sources. Results A total of 36 surface water samples were analyzed in this study, with 12 samples collected per river (Saguambi, Mindo, and Canchupí). Sampling was conducted in duplicate at two collection points per river (before and after the community) across three seasons (dry, rainy, and transitional), resulting in 4 samples per river per season. All samples showed consistently high microbial levels exceeding international guidelines at most collection points across the three rivers. The Canchupí River exhibited the highest E. coli and total coliform counts during the dry season, with values of 1.50 × 107 and 1.79 × 107 CFU/100 mL, respectively. The Saguambi River showed the highest E. coli levels in the transitional season (9.42 × 104 CFU/100 mL). The Mindo River peaked in E. coli (7.15 × 105 CFU/100 mL) and total coliforms (5.85 × 105 CFU/100 mL) after the community. Molecular analysis identified M. tuberculosis in all rivers year-round. M. leprae was found in the Saguambi and Mindo Rivers, and H. pylori was identified in both Mindo and Canchupí Rivers. Giardia and Cryptosporidium parasites’ detection varied among rivers and seasons.